Is Magnesium Supplementation an Effective Nutritional Method to Reduce Stress in Domestic Pigs? A Systematic Review - Bushby, Emily V.; Dye, Louise; Collins, Lisa M. (Frontiers in Veterinary Science, 2021)
In commercial pig production stressful events are common and can have detrimental impacts on the pig’s health and welfare, as well as performance of the farm. Supplementary magnesium may reduce stress, and subsequent harmful and aggressive behaviours, that occur during stressful events, such as regrouping. However, reports on the efficacy of this treatment are mixed. We aimed to systematically review the studies in which magnesium was given to pigs to examine the effects on measures of stress. Of sixteen studies included in the final corpus, ten reported at least one statistically significant beneficial effect of supplementary magnesium on reducing stress. However, two studies found magnesium significantly increased stress suggesting supplementary dietary magnesium may be harmful in some cases. Overall, there are a limited number of studies investigating the possible effect of magnesium on reducing stress in pigs, and although results were varied, the majority found beneficial effects of supplementary magnesium.